2017
DOI: 10.1097/bsd.0b013e3182aab1e3
|View full text |Cite
|
Sign up to set email alerts
|

Curve Characteristics and Foraminal Dimensions in Patients With Adult Scoliosis and Radiculopathy

Abstract: A correlation between curve types and symptomatic foraminal stenosis exists. Adult scoliosis patients with sciatic nerve pain typically present with foraminal stenosis at the concavity of the caudal fractional curve. Similarly, patients with femoral nerve pain present with foraminal stenosis at the concavity of the caudal fractional curve when the main structural curve is thoracic, thoracolumbar, or lumbar (apex L2 or higher).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…[20] Pugely et al showed that critically reduced foraminal size on computed tomography and curve concavity were associated with lower extremity radicular pain. [16] Here, we extend these findings to routine upright and supine radiographs and demonstrate, in a side- and level-specific manner, that smaller IPH is associated with radicular pain.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…[20] Pugely et al showed that critically reduced foraminal size on computed tomography and curve concavity were associated with lower extremity radicular pain. [16] Here, we extend these findings to routine upright and supine radiographs and demonstrate, in a side- and level-specific manner, that smaller IPH is associated with radicular pain.…”
Section: Discussionsupporting
confidence: 57%
“…In a study of 384 foraminas, Pugely et al showed that caudal lumbar foraminal stenosis <40 mm 2 was associated with sciatic nerve pain and rostral lumbar foraminal stenosis <30 mm 2 was associated with formal nerve pain. Furthermore, reduced foraminal size were associated with concavity of the curve [16]. Although direct measurements of foramina were not feasible in this study due to the lack of computed tomography in patient cohorts, IPH serves as a logical correlate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the size and shape of the foramen are often associated with symptoms of nerve root compression in the spinal region. These changes in foraminal dimensions have been commonly used to understand patho-anatomy with respect to corresponding changes in symptoms, clinical signs, or the pathophysiology of some spinal disorders [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Residual thoracolumbar/lumbar scoliosis in adult patients includes the development of back pain due to degeneration of the lower lumbar spine and neurological symptoms due to degeneration of the thoracolumbar/lumbar spine. 4 The goal of surgery is to achieve nerve decompression, correct the deformity, and improve the global alignment of the spine in the coronal and sagittal planes. Unlike AIS, corrective fixation for adult scoliosis is associated with stiffness and local kyphosis of the scoliosis curve, requiring adequate intervertebral dissection and osteotomy.…”
Section: Introductionmentioning
confidence: 99%